Book Review: Dispute Settlement in the UN Convention on the Law of the Sea - Mossop, Joanna (Victoria University of Wellington Law Review, 2019)
This article is a book review of Natalie Klein Dispute Settlement in the UN Convention on the Law of the Sea (Cambridge University Press, Cambridge, 2005) (418 pages). The law of the sea has been one of the most dynamic and disputed areas of international law for most of the past several centuries. The fact that the UN Convention on the Law of the Sea contains a dispute settlement provision that involves compulsory adjudication was a move away from the contentious past characterised by unilateral action. Mossop states that Klein has written a technically excellent text outlining the history and development of the dispute procedures, the requirement of each part of the process, and the extent to which the cases heard under the dispute procedures have cast light on the operation of the procedures. Although the book will be of significant value to practitioners and scholars dealing with this area of the law, Mossop argues that the detailed examination of the topic means that the book will not be suitable as a student textbook. It is concluded that the book is a solid foundation against which later cases can be compared.